Broadband Infrastructure and Unemployment - Evidence for Germany - Nina Czernich (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2011)
Online job search is becoming increasingly prominent and is viewed to improve the efficiency of the search process. OLS results suggest a negative association of DSL availability with unemployment rates across German municipalities. However, the roll-out of DSL networks is not random. This paper exploits the fact that the availability of DSL connections depends on a municipality's distance to the closest interconnection point to the pre-existing voice-telephony network. Instrumental-variable results using this distance as an instrument for DSL availability do not confirm the effect of DSL availability on unemployment.
urn:nbn:de:bvb:19-epub-12279-7
Keywords: J64; L96; 330; Unemployment; job search; broadband internet; Breitbandkommunikation; Geographische Entfernung; Regionaler Arbeitsmarkt; Arbeitsuche; Internet; Schätzung; Deutschland